2012
DOI: 10.1001/archgenpsychiatry.2011.1566
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frontotemporal Activation During Pain Observation in Sexual Sadism

Abstract: Context Sexual sadism is a psychiatric disorder in which sexual pleasure is derived from inflicting pain, suffering, and/or humiliation on others. While the psychological and forensic aspects of sexual sadism have been well-characterized, little is known about the neurocognitive circuitry associated with the disorder. Sexual sadists show increased peripheral sexual arousal when observing other individuals in pain. The neural mechanisms underlying this unusual response are not well understood. We predicted that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…a set of adaptive behavioral tactics through which subclinical psychopaths and Machiavellians get their own way-see Jonason & Buss, 2012;Jonason, Li, Webster, & Schmitt, 2009), sadism appears to be more indicative of a non-goal exaltation where arousal-seeking orientation is pivotal, making sadism an even more socially disturbing behavior. This non-goal exaltation has been evidenced by Harenski, Thornton, Harenski, Decety, and Kiehl (2012) who found that, contrary to non-sadists, sexual sadists showed increased activity in the left amygdala (a region of the brain involved in sexual arousal and the reward system) in response to pictures evoking pain caused by another person, compared to pictures without any kind of pain. Therefore, sadism might be associated with a pattern of moral judgments that would go beyond the inhibition of emotional aversion experienced toward harmful intent or actual harm; the exciting experience associated with such a pattern of moral judgment would possibly add incrementally to the moral distortion.…”
Section: Everyday Sadism As a Source Of Moral Impairmentmentioning
confidence: 76%
See 1 more Smart Citation
“…a set of adaptive behavioral tactics through which subclinical psychopaths and Machiavellians get their own way-see Jonason & Buss, 2012;Jonason, Li, Webster, & Schmitt, 2009), sadism appears to be more indicative of a non-goal exaltation where arousal-seeking orientation is pivotal, making sadism an even more socially disturbing behavior. This non-goal exaltation has been evidenced by Harenski, Thornton, Harenski, Decety, and Kiehl (2012) who found that, contrary to non-sadists, sexual sadists showed increased activity in the left amygdala (a region of the brain involved in sexual arousal and the reward system) in response to pictures evoking pain caused by another person, compared to pictures without any kind of pain. Therefore, sadism might be associated with a pattern of moral judgments that would go beyond the inhibition of emotional aversion experienced toward harmful intent or actual harm; the exciting experience associated with such a pattern of moral judgment would possibly add incrementally to the moral distortion.…”
Section: Everyday Sadism As a Source Of Moral Impairmentmentioning
confidence: 76%
“…The reward-evoking effect of a victim-perpetrator state of affairs is well supported by various neuroscientific evidences. For instance, neuroimaging studies highlighted that sadists showed increased activity in the left amygdala-a region involved in sexual arousal and reward-in response to pictures evoking pain caused by another person (Harenski et al, 2012). The authors also found increased amygdala (a region associated with emotions) activity in sadists only, suggesting that these individuals derived also pleasure (a more general positive emotion than sexual arousal) from seeing such pictures.…”
Section: Causal Scenariomentioning
confidence: 99%
“…Beyond existing literature on the processing of empathy-inducing stimuli in healthy populations, there may be additional cortical or subcortical brain regions that contribute to abnormal processing of these regions in psychopathy. For instance, the ventral striatum has been found to be over-reactive in adolescents with conduct disorder as well as sexual sadists (Decety et al, 2009; Harenski et al, 2012). Therefore, coordinates for the ventral striatum were selected from a recent meta-analysis of fMRI studies (Diekhof et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…This research is the first to document such a pattern among everyday sadists. It represents a clear departure from the psychology of disordered sadism, as severe sexual sadists show an opposite tendency to exaggerate others' suffering (Harenski, Thornton, Harenski, Decety, & Kiehl, ) . Our results may simply reflect a response bias generated by the nature of the rating task.…”
Section: Limitations and Recommendations For New Directionsmentioning
confidence: 99%